2004
DOI: 10.1029/2003jd004387
|View full text |Cite
|
Sign up to set email alerts
|

A modeling study of aqueous production of dicarboxylic acids: 1. Chemical pathways and speciated organic mass production

Abstract: While the formation pathways and thermodynamic properties of inorganic species (e.g., sulphate) in atmospheric aerosols are well understood, many more uncertainties exist about organics. In the present study we present oxidation pathways of organic gas phase species that lead to low volatility organic compounds (C2‐C6 dicarboxylic acids, pyruvic acid) in both the aqueous and gas phases. This mechanism is implemented in a cloud parcel model initialized with pure (NH4)2SO4 particles in 10 discrete sizes. Under c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

18
439
4

Year Published

2007
2007
2015
2015

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 342 publications
(461 citation statements)
references
References 103 publications
18
439
4
Order By: Relevance
“…60±70 ng m -3 ) at night. Glyoxal (Gly) and methylglyoxal (MeGly) are produced by gaseous-phase oxidation from various VOCs including ethylene (Ervens et al, 2004), and toluene, benzene, xylene (Volkamer et al, 2001) as well as terpenes (Fick et al, 2004) and isoprene (Zimmermann and Poppe, 1996). Interestingly, Gly showed higher concentrations in daytime whereas MeGly is more abundant in nighttime (Table 2).…”
Section: α-Dicarbonylsmentioning
confidence: 99%
“…60±70 ng m -3 ) at night. Glyoxal (Gly) and methylglyoxal (MeGly) are produced by gaseous-phase oxidation from various VOCs including ethylene (Ervens et al, 2004), and toluene, benzene, xylene (Volkamer et al, 2001) as well as terpenes (Fick et al, 2004) and isoprene (Zimmermann and Poppe, 1996). Interestingly, Gly showed higher concentrations in daytime whereas MeGly is more abundant in nighttime (Table 2).…”
Section: α-Dicarbonylsmentioning
confidence: 99%
“…Kawamura and Ikushima (1993) suggested that oxidation of volatile organic compounds (VOCs) is the major source of low molecular weight (C 2 -C 6 ) diacids observed at an urban site in Tokyo, based on the seasonal variation of these diacids. More recently, Ervens et al (2004) proposed that cloud processing could be an important source of low molecular weight diacids, although there are still many uncertainties in the production pathway of these compounds.…”
Section: Introductionmentioning
confidence: 99%
“…Clouds and aqueous aerosols provide an efficient medium for liquid phase reactions of water soluble species: more than 60% of the total sulfate on a global scale is estimated to be produced from aqueous phase oxidation of SO 2 (Kanakidou et al, 2005). Recent studies suggest that, as sulfate, SOA can also be produced through aqueous phase reactions in clouds, fogs and aerosol water (Blando and Turpin 2000;Ervens et al 2003;Ervens et al 2004a;Ervens et al 2004b;Ervens et al 2008;Gelencsér and Varga 2005;Lim et al 2005;Altieri et al 2006;Altieri et al 2008;Carlton et al 2006;Carlton et al 2007;Poulain et al, 2007;Liu et al, 2009;El Haddad et al 2009;Poulain et al 2010). Briefly, reactive organics are oxidized in the interstitial spaces of clouds to form highly water-soluble compounds (e.g.…”
Section: Aqueous-phase Reactions Of Organic Compoundsmentioning
confidence: 99%